Egemonia senza “Principe”. Su Raniero Panzieri “traduttore” di Gramsci (1944-1959) - Guzzone, Giuliano (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2020)
This essay deals with Raniero Panzieri’s interpretation of Gramsci, focusing on the period 1944-1959. In this period Panzieri made his career in the Italian Socialist Party and became one of the leading figures of the socialist cultural politics. The period was also marked by great historical events, in Italy and abroad: the crisis of Frontism, the process of “de-Stalinization”, the “Hungarian facts” and the “neo-capitalist” revolution (§ 1). So, it is not surprising that Panzieri’s approach to Gramsci has known a “qualitative leap” in the years between 1953 and 1959, by touching several issues – democratic journalism, culture-politics (theory-practice, intellectuals-masses) linkage, alliance of subaltern classes, consiliarism – and trying to “translate” them in a different “historical language” (§§ 3-4). The previous period (1944-1952) was instead a period of investigation and research: the first edition of Gramsci’s works and other publications allowed Panzieri to be acquainted with the Anti-Croce and the position on the “Southern Question” (§ 2); but Panzieri’s cultural work was influenced also by the mass political work he carried out in Sicily in the same years. The conclusion is that Panzieri’s peculiar “Gramscism” consisted first of all in the attitude to consider the theory-practice unity not only a theoretical and ideological question, but also and above all a practical, political and organizational one (§ 5). Autonomy of culture, Consiliarism, Hegemony, Philosophy of praxis, Subaltern classes